ANALYSIS OF LAND COVER (LULC) DYNAMICS OF A SPECIFIC AREA BASED ON GIS AND REMOTE SENSING TECHNOLOGIES - Azamjon Jobborov; Azamat Khoshimov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Land use and land cover (LULC) changes represent a critical challenge for sustainable environmental management, urban planning, and ecosystem conservation under conditions of rapid population growth and socio-economic transformation. This article provides a comprehensive analysis of LULC dynamics within a specific geographic area based on the integration of Geographic Information Systems (GIS) and remote sensing technologies. The study synthesizes recent scientific literature to examine methodological approaches, data sources, and analytical techniques used for detecting and monitoring spatial and temporal land cover changes. Particular emphasis is placed on the application of multi-temporal satellite imagery, high-resolution data, and advanced classification methods, including machine learning algorithms, to improve accuracy and interpretability of LULC assessments. The review also highlights the influence of socio-economic drivers, policy decisions, and climatic factors on land use transformations, emphasizing the need for interdisciplinary and localized case studies. The findings demonstrate that GIS and remote sensing provide robust and efficient tools for understanding complex land cover dynamics and support evidence-based decision-making for sustainable land management. The article concludes by identifying existing research gaps and proposing directions for future studies that integrate technological innovation with socio-environmental perspectives.